FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA IBU HAMIL DI PUSKESMAS NUNPENE KABUPATEN TIMOR TENGAH UTARA TAHUN 2018 - FLORA NAIBAHO, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
Pregnancy problems can result in a risk of maternal mortality (AKI). One result of high levels of AKI due to hypertension in pregnancy or pre-eclampsia / eclampsia in addition to bleeding, and infection. The purpose of the study was to determine the factors related to the incidence of hypertension in pregnant women at the Nunpene Health Center in North Central Timor District in 2018. The research method uses analytical surveys with case control or case and control approaches, using primary data with questionnaires and secondary data by taking data on pregnant women who have hypertension. This research was carried out in Juny-August 2018 at the Nunpene Health Center in North Central Timor District. The population in this study were all pregnant women who had hypertension in 2017 totaling 30 cases. The sample of this study was for the case of 30 people, and for the control of 30 people, the sampling technique for the case was total sampling and for control was simple random sampling. Univariate analysis to determine the frequency distribution of each variable, and bivariate analysis with Chi Square and 95% confidence level (? <0.05). The results of the study showed a relationship between age (0.045), history of hypertension (0.010), nutritional status (0.037), parity (0.020) with the incidence of hypertension. While the job variable is not associated with the incidence of hypertension (0.774).There is a relationship between age,), history of hypertension, nutritional status, parity with the incidence of hypertension in pregnant women. Hypertension in pregnancy is a dangerous disease, especially if it occurs in women who are pregnant. This can cause death for the mother and baby to be born.